PENGARUH KUALITAS PELAYANAN, HARGA, LOKASI TERHADAP MINAT MEMBELI ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Cici Ayu Tania; Hafizah; Bunga Aditi (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This research aims to find out the influence of person job fit and person organization fit on organizational citizenship behavior (OCB) mediated organizational commitment to PPKS Medan employees. The population in this study was 135 people, using saturated sample techniques, samples were obtained as large as the total number of MedanPPKS employees. The analytical technique used is path analysis. While the type of research used in this study is associative with a quantitative approach, the method used in this study is statistics with data retrieval techniques through questionnaires onall employeesof PPKS Medan. The results showed that person job fit had a positive and significant effect on OCB (t count 3,752 and significance 0.000<0.05). Person organization fit positively and significantly affects OCB (t count 4,731 and significance 0.000<0.05). Person job fit has a positive and significant effect on organizational commitment (t count 6,196 and significance 0.000<0.05). Person organization fit has a positive and significant effect on organizational commitment (t count 13,306 and significance 0.000<0.05). Organizational commitment has a positive and significant effect on OCB (t calculate 4,449 and significance 0.000<0.05). Organizational commitment has an effect on mediating person job fit against OCB (direct influence value 0.159 < indirect influence 0.210). Organizational commitment has no effect on mediating person organization fit against OCB (direct influence value 0.225 > 0.007).